2019
DOI: 10.1016/j.ultramic.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

On the depth resolution of transmission Kikuchi diffraction (TKD) analysis

Abstract: In this paper, we have analysed the depth resolution that can be achieved by 'on-axis' transmission Kikuchi diffraction (TKD) using a Zr-Nb alloy. The results indicate that the signals contributing to detectable Kikuchi bands originate from a depth of approximately the mean free path of thermal diffuse scattering (λTDS) from the bottom surface of a thin foil sample. This existing surface sensitivity can thus lead to the observation of different grain structures when opposite sides of a nano-crystalline foil ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Data were collected on the Zeiss Sigma300 field emission gun scanning electron microscope (FEG-SEM) with an accelerating voltage of 30 kV, working distance of 3 mm and with the sample in the TKD holder normal to the electron beam. High-resolution TKD patterns were obtained in regions of samples (parallel and perpendicular to the loading direction), which showed high dislocation activity covering a hard−soft grain pair in a Zeiss Merlin FEG SEM equipped with a Bruker on-axis Optimus detector 55,56 . The Kikuchi patterns were further subdivided into 20 regions of interest (selected to ignore the area in the centre of the pattern resulting from the direct electron beam) and cross-correlated with reference patterns selected in a region away from any significant interest in the image map as described in refs.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected on the Zeiss Sigma300 field emission gun scanning electron microscope (FEG-SEM) with an accelerating voltage of 30 kV, working distance of 3 mm and with the sample in the TKD holder normal to the electron beam. High-resolution TKD patterns were obtained in regions of samples (parallel and perpendicular to the loading direction), which showed high dislocation activity covering a hard−soft grain pair in a Zeiss Merlin FEG SEM equipped with a Bruker on-axis Optimus detector 55,56 . The Kikuchi patterns were further subdivided into 20 regions of interest (selected to ignore the area in the centre of the pattern resulting from the direct electron beam) and cross-correlated with reference patterns selected in a region away from any significant interest in the image map as described in refs.…”
Section: Methodsmentioning
confidence: 99%
“…The sampling depth is the maximum depth from which the diffraction pattern is collected. Recently, Liu et al reported that the sampling depth is linearly proportional to the elastic scattering mean free path ( λ ), and their relationship is d ≈ 3.5 λ in all elements (Liu et al, 2019). As elastic scattering is usually coherent, it is important to determine the sampling depth because both the spot patterns in PED and Kikuchi bands in TKD are generated by the coherent scattering of electrons when electrons escape the sample surface by the final diffraction event.…”
Section: Resultsmentioning
confidence: 99%
“…If a nanocrystalline film consists mainly of columnar grains, the difference between TEM-PED and SEM-TKD orientation maps would not be so large. For light elements, in particular, the signal from the whole thickness can be collected in both PED and TKD, e.g., d ≈ 80 nm for Al at 30 kV (Sneddon et al, 2017), because λ is only dependent on the element and electron energy but independent of the sample thickness (Liu et al, 2019). However, if a nanocrystalline film consists of heavy elements with multiple overlapping 3D grains along the electron beam path, the difference between TEM-PED and SEM-TKD orientation maps becomes significant due to the different sampling depths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the diffraction patterns in TKD are produced by the material closest to the exit surface of the electron beam in the sample (Rice et al, 2014; Liu et al, 2019). Recent work has shown that for higher atomic number targets like Pt, the depth from which the TKD patterns arise is between 5 and 12 nm (Sneddon et al, 2017; Liu et al, 2019). This is schematically shown in Figure 6a.…”
Section: Discussionmentioning
confidence: 99%